PENGARUH KEBIJAKAN DIVIDEN, STRUKTUR MODAL, DAN RASIO LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2019 – 2023 - Umar Hi Salim; Ikayanti Puspaning; Nicco Agustinus Gunawan (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2026)
This study aims to determine and analyze the effect of dividends, capital structure, and liquidity ratios on firm value in manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023. The research question is whether dividends, capital structure, and liquidity ratios, partially and simultaneously, affect firm value. The sample size for this study was 74 listed companies in the manufacturing sector. The data collection method used was secondary data obtained from the Indonesia Stock Exchange's receipts page and the respective companies. The analytical tools used in this study use multiple linear regression analysis models, correlation coefficients, determination coefficients, and hypothesis testing using the t-test and F-test processed using the IBM SPSS version 25 program. Based on the results of the data analysis, it can be concluded that (1) simultaneously, Dividend Policy, Capital Structure and Liquidity Ratio affect Company Value by 14.4%, while the remaining 85.4% is influenced by other variables not included in the study (2) Partially, Dividend Policy affects Company Value, then Capital Structure and Liquidity Ratio do not affect Company Value.